2015
DOI: 10.1186/s13075-015-0669-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes reflect clinical response in a placebo-controlled randomized trial of abatacept in patients with diffuse cutaneous systemic sclerosis

Abstract: IntroductionSystemic sclerosis is an autoimmune disease characterized by inflammation and fibrosis of the skin and internal organs. We sought to assess the clinical and molecular effects associated with response to intravenous abatacept in patients with diffuse cutaneous systemic.MethodsAdult diffuse cutaneous systemic sclerosis patients were randomized in a 2:1 double-blinded fashion to receive abatacept or placebo over 24 weeks. Primary outcomes were safety and the change in modified Rodnan Skin Score (mRSS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 22 publications
6
82
1
Order By: Relevance
“…A growing body of evidence supports the use of skin, lung, and peripheral blood transcriptomes as SSc biomarkers to quantify interpatient heterogeneity, to identify dysregulated molecular pathways underlying disease, and to identify appropriate patients for specific SSc therapies (6)(7)(8)(9). These studies have identified remarkable homogeneity in skin biopsies obtained from the same patient such that transcriptomic profiles of clinically unaffected back and clinically affected forearm biopsies are nearly identical (10)(11)(12).…”
Section: Introductionmentioning
confidence: 92%
“…A growing body of evidence supports the use of skin, lung, and peripheral blood transcriptomes as SSc biomarkers to quantify interpatient heterogeneity, to identify dysregulated molecular pathways underlying disease, and to identify appropriate patients for specific SSc therapies (6)(7)(8)(9). These studies have identified remarkable homogeneity in skin biopsies obtained from the same patient such that transcriptomic profiles of clinically unaffected back and clinically affected forearm biopsies are nearly identical (10)(11)(12).…”
Section: Introductionmentioning
confidence: 92%
“…Adverse events were similar in both groups, with one serious adverse event in the treatment group (supraventricular tachycardia), considered to be unrelated to the study drug and the patient completed the study. Patients who improved with abatacept mapped to the inflammatory intrinsic subset of skin gene expression at baseline and showed decreased gene expression after treatment, mainly in genes related to CD28 T-cell co-stimulation, whereas non-improvers and the placebo group showed stable or reverse inflammatory gene expression [51].…”
Section: T-cellsmentioning
confidence: 99%
“…Improvement in mRSS was defined as ≥30% from baseline; skin biopsies were obtained for differential gene expression and intrinsic gene expression subset assignment (inflammatory signature, fibroproliferative signature and normal-like signature). This included biopsies from four healthy controls [51].…”
Section: T-cellsmentioning
confidence: 99%
“…First, since SSc is a rare disease, clinical trials tend to have small sample sizes. Thus, few differentially expressed genes (DEGs) can be detected after multiple hypothesis testing correction (Chakravarty et al, 2015;Gordon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To gain mechanistic insight into the action of experimental therapies, clinical trials in SSc have collected genome-wide gene expression data from skin biopsies pre-and post-treatment (Chakravarty et al, 2015;Gordon et al, 2015;Rice et al, 2015a;Hinchcliff et al, 2013;Chung et al, 2009) (Martyanov et al Submitted). However, these studies in clinical trials face limitations.…”
Section: Introductionmentioning
confidence: 99%